A COMPARATIVE STUDY OF THE IMPLEMENTATION OF CORPORATE SOCIAL . RESPONSIBILITY (CSR) BETWEEN THE MALAYSIAN AND THE INDONESIAN CORPORATIONS: COMMUNICATION PERSPECTIVE STUDI KOM PARAS I APLIKASI CORPORATE SOCIAL RESPONSIBILITY (CSR) ANTARA PERUSAHAAN MALAYS - Prajarto, Nunung ([Yogyakarta] : Lembaga Penelitian dan Pengabdian Kepada Masyaraka, 2009)
Corporate social responsibility has become a sensitive issue for most corporations. in which the corporations are usually demanded to combat proverty. to prevent environment degradation and to develop business with the local communities. The study of comparison on corporate social responsibility application between the Malaysian and Indonesian corporations is conduded in compliance with content analysis and case study methods. These explores the process of planning. delivering. and evaluating the corporate social responsibility programs established by Maybank, Bank Mandiri. Riau Andalan Pulp and Paper. Telekom Malaysia and Indosa!, as well as the publications related to the corporations. The findings of the study indicate that there are differences between the Malaysian and Indonesian corporations in stressing the application of corporate social responsibility programs and in paying attention on the development of nation state and charader building. The result of the study also recommends the production of a comprehensive report of the application corporate social responsibility for each corporation and the implementation of three potential models in the planning process of corporate social responsibility programs.